2018
DOI: 10.15252/emmm.201708163
|View full text |Cite
|
Sign up to set email alerts
|

An FGFR 3/ MYC positive feedback loop provides new opportunities for targeted therapies in bladder cancers

Abstract: FGFR3 alterations (mutations or translocation) are among the most frequent genetic events in bladder carcinoma. They lead to an aberrant activation of FGFR3 signaling, conferring an oncogenic dependence, which we studied here. We discovered a positive feedback loop, in which the activation of p38 and AKT downstream from the altered FGFR3 upregulates MYC mRNA levels and stabilizes MYC protein, respectively, leading to the accumulation of MYC, which directly upregulates FGFR3 expression by binding to active enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 70 publications
6
34
1
Order By: Relevance
“…Results indicated that the mRNA expression levels of MYC, HMGA1, IGF1R, and INSR were significantly decreased after inhibition of GClnc1 in bladder cancer cells. MYC was the lowest down-regulated oncogene after inhibition of GClnc1 in bladder cancer cells and has been proven to be a vital regulator of bladder cancer progression (27)(28)(29). Thus, in this study, the LIN28B/let-7a/MYC pathway was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that the mRNA expression levels of MYC, HMGA1, IGF1R, and INSR were significantly decreased after inhibition of GClnc1 in bladder cancer cells. MYC was the lowest down-regulated oncogene after inhibition of GClnc1 in bladder cancer cells and has been proven to be a vital regulator of bladder cancer progression (27)(28)(29). Thus, in this study, the LIN28B/let-7a/MYC pathway was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…7C, D). MYC has been well characterized as a critical regulator of cancer progression and invasion in bladder cancer (27)(28)(29). Thus, MYC was chosen for the further study.…”
Section: Down-regulation Of Gclnc1 Increased Let-7a Expression and Dementioning
confidence: 99%
“…50,51 Activation of this signaling was actually found to be enriched in a subset of bladder cancer, 17,36,52 and rather considered targetable and druggable. 53,54 Further studies are required to validate alterations in these genes as chemosensitivity biomarkers and explore possible mechanisms of sensitivity caused by the activation of these signaling pathways. Predictive biomarkers reported so far for CDDP sensitivity in bladder cancer have not been consistent among studies, potentially because of the reliance on small cohorts, retrospective or post-hoc analyses, the difference in chemotherapy regimens, outcome measurements and sequencing techniques, consequently producing conflicting results.…”
Section: Ddr Genesmentioning
confidence: 99%
“…To identify genes regulated by FGFR3 with different mutations, MGH-U3 and UMUC-14 bladder cancer cells endogenously expressing FGFR3-Y375C and FGFR3-S249C, respectively, were transfected for 72 hrs with three FGFR3 siRNAs (described in Mahe et al [15]). mRNA was extracted and purified with the RNeasy Mini kit (Qiagen).…”
Section: Functional Comparison Of Fgfr3 With S249c Versus Y375c Mutatmentioning
confidence: 99%
“…mRNA was extracted and purified with the RNeasy Mini kit (Qiagen). Total RNA (200 ng) from control and siRNA-treated MGH-U3 and UMUC-14 cells was analyzed with the Affymetrix human exon 1.0 ST array and the Affymetrix U133 plus 2 array, respectively, as previously described [15]. Experiments using MGH-U3 cells have been described by Mahe et al [15] and the microarray data were available from GEO (https://www.ncbi.nlm.nih.gov/geo/) under accession number GSE84733.…”
Section: Functional Comparison Of Fgfr3 With S249c Versus Y375c Mutatmentioning
confidence: 99%